Quality harvesting in the basement cut of sugarcane soil management systems - Reis, Gustavo Naves dos; Voltarelli, Murilo Aparecido; Silva, Rouverson Pereira da; Toledo, Anderson de; Lopes, Afonso (Comunicata Scientiae, 2015)
The mechanized harvesting of sugarcane has relevance across the crop production process and can be influence the cutting quality base for soil management systems. This study aimed to assess the damage caused to the mechanical harvesting of ratoon sugarcane raw relative wear of the base shear knives and soil management. The experimental design was completely randomized, factorial divided into two schemes which are: 2 different soil tillage (moldboard plow + average grade and heavy harrow + average grade) x 4 times of use of knives (0-2, 2-4 , 4-6 , 2-6(1)) and 10 repetitions , and 2 soil tillage (moldboard plow + harrow heavy, and heavy harrow + average grade) x 2 cutting discs (left and right ) x 20 repetitions, forming meshes regularly spaced 27 x 23 m, amounting to 100 repeats, or 50 replicates for each treatment in order to standardize the location of the samples taken. The variables evaluated were the mass loss of the knives of the base shear mechanism and the degree of damage to brass knuckles. The quality of mechanized harvesting of cane sugar is influenced by the soil management systems. Soil management with heavy grade + average grade has the highest quality of the harvesting operation in relation to the degree of damage to brass knuckles.